Pengaruh Financial Literacy dan Hedonic Shopping Motivation Terhadap Impulsive Buying Melalui Spending Self Control Sebagai Mediasi pada Pengguna Shopee Paylater - Syifa Andarliana Putri; Umi Widyastuti; Terrylina Arvinta Monoarfa (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the effect of financial literacy and hedonic shopping motivation on impulsive buying through spending self-control as a mediator among Shopee Paylater users in DKI Jakarta. Financial literacy and hedonic shopping motivation in this study are also examined for their influence on impulsive consumption behavior that can affect purchasing decisions in e-commerce applications. This research uses a descriptive quantitative method with a survey approach via Google Form for respondent data collection. The data analysis technique used is Structural Equation Modeling (SEM) based on PLS-SEM. The results of this study reveal that financial literacy has a positive effect on spending self-control, which in turn reduces impulsive buying behavior. Additionally, hedonic shopping motivation is found to significantly influence the increase in impulsive buying, although spending self-control acts as a mediator that strengthens this impact.